Preliminary study of microwave irradiation towards oil palm empty fruit bunches biomass - Muhammad Iqbal Ahmad; Mohd Sukhairi Mat Rasat; Shahril Nizam Mohamed Soid; Mazlan Mohamed; Zairi Ismael Rizman; Mohd Hazim Mohd Amini (Universiti Malaysia Kelantan, 2016)
In this study, torrefaction via microwave irradiation was introduced towards oil palm empty fruit bunches (EFB) samples. The samples of 10 g was fed into the quartz type crucible inside the microwave with the power input limit to 385 W. Continous nitrogen up to 50 ml/min were induced and promoted the non oxidative atmosphere in the closed crucible. This proved the increased of energy properties as high 23.6 MJ/kg for torrefied samples comparable to raw 14.8 MJ/kg. On the result of proximate analysis, fixed carbon shows the increase trends whereby the volatile matter decreased. Torrefaction has been found to improve the energy properties of oil palm EFB biomass as a fuel.